Rose's Gift: Slavery, Kinship, and the Fabric of Memory. Issue 1 (3rd March 2017) - Auslander, Mark
One of the most evocative objects in the new Smithsonian National Museum of African American History and Culture is an embroidered cloth bag that has come to be known as "Ashley's Sack". Stitch-work on the bag, signed "Ruth Middleton", recounts the bag's painful history, as a gift presented by an enslaved woman, Rose, to her daughter Ashley, when Ashley was sold at age nine in South Carolina. This paper explores 'Ashley's sack' as an object of history, memory, ritual action, and aesthetic creativity.